Study on Theoretical Aspects of Enhanced Intelligent Coaching Agent in Employee Performance Appraisal in Tertiary Institutions in Nigeria - Chinwe Gilean, Onukwugha; Bethran Chibuike, Amanze; Ikechukwu Valentine, Udegbe (International Journal of Computer Sciences and Engineering, 2022)
The intelligent coaching agent for enhancing employee performance appraisal was designed to appraise the employee performance and illustrated how intelligent coaching agent – supervised learning can be used as a support tool for the assessment of employee task performance. We have shown how it provides weight score for each task and later used for the evaluation of the team performance in terms of job executed as against the expected performance. We have also indicated how it gives manager the ability to incorporate accuracy levels for the staff performance appraisal. The new system allows employee, team managers and general manager to access their performance records from any point of internet access point. The system has facilities: staff registration module, setting up of task and assigning weight scores to the task, assigning task to individuals in the team, monitoring the execution of those task, comparative analysis of the performance using supervised learning to determine the level of performance based on the assigned task against the task executed by the team. The result obtained from the testing of the new system shows a high level of accuracy in determining the team performance and rates it in percentage.